2009
DOI: 10.1501/commua1_0000000645
|View full text |Cite
|
Sign up to set email alerts
|

Vn-SLANT HELICES IN MINKOWSKI n-SPACE En1

Abstract: C o m m u n .Fa c .S c i.U n iv .A n k .S e rie s A 1 Vo lu m e 5 8 , N u m b e r 1 , P a g e s 2 9 -3 8 (2 0 0 9 ) IS S N 1 3 0 3 -5 9 9 1 V n SLANT HELICES IN MINKOWSKI n-SPACE E n 1 · ISMAIL GÖK, ÇETIN CAMCI AND H. HILMI HACISALIHO ¼ GLUAbstract. In this paper we give a de…nition of harmonic curvature functions in terms of Vn and de…ne a new kind of slant helix which we call Vn slant helix in n dimensional Minkowski space E n 1 by using the new harmonic curvature functions : Also we de…ne a vector …eld D L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Definition Let α:Idouble-struckREn be a unit speed curve with nonzero curvatures k i ( i = 1,2,…, n ) in En and let { V 1 , V 2 ,…, V n } denote the Frenet frame of the curve α . We call α a V n ‐slant helix, if the n th unit vector field V n makes a constant angle ϕ with a fixed direction X , that is, <Vn,X>=cosϕ,ϕπ2,ϕ=constant, along the curve, where X is unit vector field in En …”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition Let α:Idouble-struckREn be a unit speed curve with nonzero curvatures k i ( i = 1,2,…, n ) in En and let { V 1 , V 2 ,…, V n } denote the Frenet frame of the curve α . We call α a V n ‐slant helix, if the n th unit vector field V n makes a constant angle ϕ with a fixed direction X , that is, <Vn,X>=cosϕ,ϕπ2,ϕ=constant, along the curve, where X is unit vector field in En …”
Section: Preliminariesmentioning
confidence: 99%
“…Also some characterizations of such curves were presented in other studies . A new kind of a slant helix in Euclidean n‐space En, called V n ‐slant helix, is defined and studied in Gök et al They use the constant angle φ in between a fixed direction X and the n th Frenet vector field V n of the curve, that is, ⟨⟩Vn,X=cos φ , φπ2 and φ = constant.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there exist more special curves in the space such as slant helix which first introduced by Izumiya and Takeuchi by the property that the normal lines of curve make a constant angle with a fixed direction in the Euclidean 3-space 3 E [14]. Slant helices have been studied by some mathematicians and new kinds of these curves also have been introduced [1,11,16,17,19]. Moreover, these curves have been considered in Lorentzian spaces [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…They generalized the inclined curves in E 3 to E n , n > 3, and then gave a characterization for them: "If a curve α is an inclined curve then n−2 i=1 H 2 i = constant". And then many studies have been reported on generalized helices, inclined curves by using Hacısalihoglu's harmonic curvature functions [1] , [2] , [3] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2008,Önder et al defined a new kind of slant helix in Euclidean 4-space E 4 which they called B 2 -slant helix and they gave some characterizations of this slant helices in Euclidean 4-space E 4 [12] . And then in 2009, Gök et al defined a new kind of slant helix in Euclidean n-space E n , n > 3, which they called V n -slant helix and they gave some characterizations of this slant helices in Euclidean n-space E n [7] .…”
Section: Introductionmentioning
confidence: 99%